γδT Cells Are Required for CD8+ T Cell Response to Vaccinia Viral Infection - Dai, Rui; Huang, Xiaopei; Yang, Yiping (Frontiers in Immunology, 2021)
Vaccinia virus (VV) is the most studied member of the poxvirus family, is responsible for the successful elimination of smallpox worldwide, and has been developed as a vaccine vehicle for infectious diseases and cancer immunotherapy. We have previously shown that the unique potency of VV in the activation of CD8+ T cell response is dependent on efficient activation of the innate immune system through Toll-like receptor (TLR)-dependent and -independent pathways. However, it remains incompletely defined what regulate CD8+ T cell response to VV infection. In this study, we showed that gamma-delta T cells play an important role in promoting CD8+ T cell response to VV infection. We found that gamma-delta T cells can directly present viral antigens in the context MHC-I for CD8+ T cell activation to VV in vivo, and we further demonstrated that cell-intrinsic MyD88 signaling in gamma-delta T cells is required for activation of gamma-delta T cells and CD8+ T cells. These results illustrate a critical role for gamma-delta T cells in the regulation of adaptive T cell response to viral infection and may shed light on the design of more effective vaccine strategies based on manipulation of gamma-delta T cells.